Thermo-processable chitosan-based plastic substitute with self-adaptiveness and closed-loop recyclability. (1st September 2022) - Lin, Leyi; Su, Zhiping; Zhang, Haishan; Zhou, Guowen; Zhou, Haonan; Ren, Junli; Wang, Xiaoying; Liu, Chuanfu; Wang, Xiaohui
Abstract: The increasing environmental burden generated by disposable plastic wastes makes the development of sustainable substitute materials an emergent task. As one of the most abundant bioresources, chitosan (CS) has been considered as a potential candidate for plastic substitution. Conventionally, CS-based materials are fabricated through a solution-processing procedure due to the high crystallinity of CS. Herein, we designed a CS-based material via integrating CS into the network of polyimine (PI), which shows thermomechanical processability similar to plastics. Strong interactions were achieved through dynamic imine bond and hydrogen bond and thus formed a thermo-processable dynamic composite network. These CS-based plastic substitutes exhibit exceptional mechanical performances, excellent thermal/chemical stability, and a series of self-adaptiveness, including re-healing, reprocessing and multi-layer laminating. Notably, CPs can be easily degraded and 100% recycled for the production of next-generation materials. This work provides an alternative route to produce green and sustainable biomass materials as a plastic substitute. Graphical abstract: Unlabelled Image